Isu semasa terhadap hubungan sosial dengan non Muslim di Malaysia daripada perspektif hukum Islam / Khairul Azhar Meerangani - Khairul , Azhar Meerangani (2016)
This study describes current issues in social relations between Muslims and non-Muslims in Malaysia according to Islamic law, focusing on issues that occurred after the 12th general election involving religious issues, social, legal and business. The aim of this study is to identify and analyze the issues that underlie the relationship between this two groups based on the rule of Islamic law. Three main methodologies have been applied in this study : Firstly, documents analysis methods for obtaining data pertaining to the rights of non-Muslim citizens of the Islamic perspective and the Federal Constitution. Secondly, current issues were identified through interviews and from printed and electronic media to get the real picture of the background of those issues. Thirdly, data were being analyzed using the inductive method to produce general conclusions on the issues as well as the comparative method in comparing the views of classical and contemporary scholars on the issue. The study show that issues that frequently occur involving the relationship between Muslims and non-Muslims in Malaysia are caused by two main factors, which are confusion and ignorance of the practice of the adherents of different religions and provocation made by certain groups and parties to achieve their narrow interests through exploitation of the issues that occur. This study show that solution of issues pertaining to Muslims and non Muslims cannot be conducted without prior research on the background and on factors affecting these issues to produce a resolution that corresponds to the current reality in Malaysia.